Proficiency of Broccoli (Brassice oleracea) Juice in Recovering of Testosterone Andriol-Induced Polycystic Ovary Syndrome Rats - J. M. S. Al-Shahery, Nahla; A. Salih, Roqaya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The current study was designed to evaluate the efficiency of broccoli plant in therapy of PCOS that induced for the first time by testosterone andriol (T.A).   Forty-eight immature female rats (21 days old) were divided into 6 groups (8 rats each) as follows: G1, animals were injected with sesame oil for 39 cascade days (control). G2, animals were injected with 1mg/100g b.w of T.A for 39 cascade days. G3, animals were injected with 1mg/100g b.w of T.A gathered with gavaged broccoli juice (b.j) for 39 cascade days. G4, animals were injected with sesame oil for cascade 39 days at the end of last injection were gavaged with d.w for 30 cascade days. G5, animals were injected with 1 mg/100g b.w of T.A for 39 cascade days and at the end of last injection were gavaged with d.w for 30 cascade days. G6, animals were injected with 1mg/100g b.w of T.A for 39 days and at the end of the last injection were gavaged with b.j for 30 cascade days. T.A-induced PCOS rats (G2 and G5) in comparison with controls (G1 and G4) exhibited that had a significant (Pâ‰¤0.01) increase in the b.w, ovarian, uterine and fat pads weights as well as the fat cells diameter. Additionally, these groups had acyclicity, high numbers of ovarian cysts, atretic and preantral follicles in the ovaries, lowering the number and the diameter of C.L., and uterine changes. The levels of T, E and LH, an insulin, glucose, LDL, cholesterol in the serum were increased whereas the levels of FSH, LDH were decreased.   Therefore, T.A PCOS model could be appropriated for studied all the features of syndrome i.e, ovarian, metabolic and endocrinologiccal disturbances. Whereas all these measurements of G3 and G6 were ameliorated and recovered into their normalcy. Our findings have shown the benefit of consuming broccoli in the protection (G3) and prevention (G6) of PCOS.